Health Accessibility In Rural Areas For The Elderly In Indonesia - Natasya Nazla Prasetyo; Keren Stelin Maliangkay; Putri Andini Novianti; Risma Pertiwi; Sarah Rania Annisa (Pusat Riset dan Inovasi Nasional, 2023)
The health services between urban and rural areas are quite interesting because they have many differences that can be seen, especially the gap between the two areas. One of the characteristics of urban and rural areas is accessibility development, urban areas tend to develop faster than rural areas. This article was created with the aim of knowing the condition of health service facilities in rural areas in Indonesia and their access, especially for the elderly. The search strategy used in this research is a systematic literature review. The disparity in the elderly's use of health facilities are impacted by their education level, socioeconomic status, ownership of insurance, distance traveled, and cost of transportation. In conclusion, access to healthcare is crucial in Indonesia, particularly for elderly people living in rural areas. The Indonesian government must evenly distribute medical facilities in rural areas and guarantee universal coverage with National Health Insurance. To improve elderly health care, the government needs to develop sufficient expertise with health and social care workers with the necessary training in integrated care services.